Dye Degradation and Sulfur Oxidation of Methyl Orange and Thiophenol via Newly Designed Nanocomposite GQDs/NiSe-NiO Photocatalyst Under Homemade LED Light - Srivastava S.; Yadav R.K.; Pande P.P.; Singh S.; Chaubey S.; Singh P.; Gupta S.K.; Gupta S.; Kim T.W.; Tiwary D. (My University, 2025)
Photocatalytic processes triggered by graphene-based photocatalysts under solar light have sparked interest as a new sort of instrument for solar chemical synthesis. Herein we investigated self-assembled graphene quantum dots (GQDs)/NiSe-NiO composite photocatalyst for organic transformation as well as dye degradation. The synthesized GQDs/NiSe-NiO composite photocatalyst has an excellent suitable band gap, high molar extinction coefficient, low toxicity and chemical/thermal stability. The GQDs/NiSe-NiO composite photocatalyst emerges as a new standard for sulfur oxidation and dye degradation reactions under homemade LED light with high yield. © 2023 American Society for Photobiology.